2022
DOI: 10.3390/nano12193293
|View full text |Cite
|
Sign up to set email alerts
|

Serratula coronata L. Mediated Synthesis of ZnO Nanoparticles and Their Application for the Removal of Alizarin Yellow R by Photocatalytic Degradation and Adsorption

Abstract: In this study, the potential of biogenic zinc oxide nanoparticles (ZnO NPs) in the removal of alizarin yellow R (AY) from aqueous solutions by photocatalytic degradation, as well as adsorption, was investigated. The synthesized ZnO NPs were prepared by the simple wet-combustion method using the plant extract of Serratula coronata L. as a reducing and stabilizing agent and characterized by powder X-ray diffraction, scanning electron microscopy, energy dispersive X-ray and X-ray photoelectron spectroscopy. Photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 76 publications
(82 reference statements)
4
20
0
Order By: Relevance
“…By employing the Kubelka–Munk equation, the optical band gap is calculated which is expressed in eq . F false( R false) = α / s = false( 1 R 2 false) / 2 R where F ( R ) represents the Kubelka–Munk function, α is the absorption coefficient, s denotes the scattering factor, and R denotes the reflectance of a material. The estimated band gap value for as-synthesized Aerva persica-mediated ZnO nanoparticles agrees with recently reported studies and was found to be 3.18 eV …”
Section: Resultssupporting
confidence: 90%
“…By employing the Kubelka–Munk equation, the optical band gap is calculated which is expressed in eq . F false( R false) = α / s = false( 1 R 2 false) / 2 R where F ( R ) represents the Kubelka–Munk function, α is the absorption coefficient, s denotes the scattering factor, and R denotes the reflectance of a material. The estimated band gap value for as-synthesized Aerva persica-mediated ZnO nanoparticles agrees with recently reported studies and was found to be 3.18 eV …”
Section: Resultssupporting
confidence: 90%
“…Similarly, the high-resolution XPS spectrum of the Zn 2p region in ZnO nanoparticles displays two tting peaks located at approximately 1043.6 and 1020.5 eV, corresponding to Zn 2p 1/2 and Zn 2p 3/2 , respectively. 34 Furthermore, the XPS spectrum of the O 1s region in ZnO nanoparticles shows an asymmetrical peak centered at about 529.6 eV. These results from the core-level Zn 2p and O 1s spectra are in good agreement with previous data and conrm the ZnO structure.…”
Section: Study Of the Structure And Composition Of Biogenic Metal Oxi...supporting
confidence: 89%
“…33 Despite the abundant presence of secondary metabolites in SCR, which are known to be capable of reducing metal ions, this plant remains relatively understudied as a potential precursor for the biogenic synthesis of catalytically active metal oxide nanoparticles. 34,35 In recent studies, various biogenic nanomaterials have been explored for the removal of lead (Pb) ions, yet the utilization of indigenous plant sources to develop environmentally friendly wastewater treatment technologies remains a pressing objective for every nation. This study aims to provide essential insights into the optimal conditions for the collection and extraction of SCR, and subsequently, to investigate the efficacy of biogenic ZnO and CuO nanosized adsorbents in the removal lead(II) ions from aqueous media under bath mode conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that the Freundlich model can describe the experimental data of the adsorption isotherm whether adsorption takes place on homogeneous or heterogeneous sites and is not controlled by monolayer formation. According to this model, the adsorption centers have different energies; therefore, the active sorption sites with maximum energy were filled first followed by the others [ 92 ]. Figure 10 b shows experimental data adapted to the linear Freundlich equation.…”
Section: Resultsmentioning
confidence: 99%